Penerapan Gmp Dan Ssop Pada Industri Rumah Tangga Bakso Ikan Di Desa Harapan Kecamatan Pemangkat - Abdurrahman; Anggi; Hairulaila; Nadia; Nazri; Merdekawati, Dewi (Jurnal Perikanan dan Kelautan, 2025)
The household-scale food industry plays an important role in the economy in Indonesia, especially in the utilization of abundant fishery resources. This study aims to evaluate the implementation of GMP (Good Manufacturing Practices) and GHP (Good Hygiene Practices) in the production of fish balls in Harapan Village, Pemangkat District. This study uses observation, interview, and evaluation check-list methods based on CPPOB standards. The results of the study indicate several aspects that are not yet optimal such as location, buildings and facilities, food labeling, supervision, recording and documentation, and employee training. The results show that the fish ball household industry still has many findings that are not in accordance, indicating that the industry has not fully met the applied CPPOB standards.